PENINGKATAN KEMAMPUAN BERPIKIR KREATIF SISWA MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) - Toto, Mefe Lorina Agnes; Zulfikar, Ryan Nizar; Syarief, Nur Hasanah; Muh, Abdul Syahril (Program Studi Pendidikan Matematika, Universitas Muhammadiyah Kupang, 2024)
This classroom action research aimed to determine students’ creative thinking skills at eighth grade of C class in SMP Swasta Muhammadiyah Kupang after applying the Problem Based Learning (PBL) model. The subjects of the study were 20 students of VIIIC. The study was conducted in one cycle through four stages, namely planning, action, observation, and reflection. The instruments in this study were observation sheets and tests. The study showed an improvement in learning activities with an average percentage of 91.25%. Based on the test results, the excellent category reached 75% (15 students), the good category with 20% (4 students), and the very poor category was 5% (1 student). Besides, students' creative thinking was increased from the precycle with fluency and flexibility indicators of 28% to 50%, originality and elaboration indicators of 11% to 39%.